Plant Cell Wall Research Related to Evolution and Chemical Defenses - Dietrich, Sonia M. C.; Buckeridge, Marcos S.; Tiné, Marco Aurélio; Young, Maria Cláudia M.; Bolzani, Vanderlan da Silva [UNESP]; Braga, Marcia R.; Marques, Maria Rita (My University, 1998)
The plant cell wall is composed mainly of polysaccharides some constituted of repeating units of a single sugar, as cellulose or by two or more sugars grouped in repeating oligosaccharide blocks as the galactomannans and xyloglucans. Variations in composition and fine structure of these cell wall polysaccharides have been used as taxonomic markers and in the comprehension of the evolutive process, particularly in the Leguminosae. Partial hydrolysis of these compounds give rise to oligomers, some of which are capable of eliciting the synthesis of defensive substances in plants named phytoalexins. Species which differ in respect to phytoalexin liberation also differ in cell wall composition, particularly in the pectic fraction of the wall. Pectinases (mainly endopolygalacturonases) present in fungi, have been shown to hydrolyze plant cell walls yielding phytoalexin-eliciting oligosaccharides which differ in composition and in eliciting capacity in different species. These differences can be associated with the capacity of a given species to produce phytoalexins. On the other hand, the phytoalexin induction in plants is being used as a method of producing novel bioactive secondary metabolites.
Keywords: Carbohydrates; Cell wall; Phytoalexins; Secondary metabolites